O ENSINO DE FÍSICA DE PARTÍCULAS ELEMENTARES COMBINANDO AS METODOLOGIAS ENSINO SOB MEDIDA E INSTRUÇÃO PELOS COLEGAS - Vicentini, Alexandre (2019)
In this work the potentialities of a teaching process combining the Just−In−Time Teaching (JiTT) and Peer Instruction (PI) methodologies, mediated by the Information and Communication Digital Technologies (ICDT), on the teaching of Elementary Particle Physics were analyzed. The activities developed in the didactic sequence made it possible to gather testimony and perform diagnoses. The interaction between the students, made possible by the PI methodology, promoted debates that made the class richer and more dynamic, improving performance and the relationship between students. The use of electronic resources has aroused the interest and curiosity of the students, despite the low or no ability of many of them in front of these resources. Tools such as Google Drive, Google Forms, Plickers, and WhatsApp have enabled the optimization of activities inside and outside the classroom, as well as maintaining a constant dialogue between the teacher-researcher and students. However, some obstacles have arisen like the lack of structure and working conditions as major obstacles to applying new methodologies in the schools. The testimonies revealed that JiTT contributed to an important aspect in teaching, extraclassed study. A pre-test, a post-test and an opinion were applied. The results of the pre-test and the post-test revealed a learning gain of the students compatible with those adopted in the literature for classes submitted to active learning methodologies. The opin-ion showed that time was one of the greatest difficulties faced by the students. Despite the difficulties, the students welcomed the proposal of this work and showed interest in using the methodology presented with other contents. Therefore, this research has brought contributions to the teaching of Elementary Particle Physics, a theme that is worked weakly in the high school, and that it can serve as a support to other teachers whose objective is to teach, in an attractive way, dynamic andtechnology, modern Physics contents.